2012
DOI: 10.1103/physrevb.85.121406
|View full text |Cite
|
Sign up to set email alerts
|

Atomic control of strain in freestanding graphene

Abstract: In this study, we describe a new experimental approach based on constant-current scanning tunneling spectroscopy to controllably and reversibly pull freestanding graphene membranes up to 35 nm from their equilibrium height. In addition, we present scanning tunneling microscopy (STM) images of freestanding graphene membranes with atomic resolution. Atomic-scale corrugation amplitudes 20 times larger than the STM electronic corrugation for graphene on a substrate were observed. The freestanding graphene membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 38 publications
6
96
0
1
Order By: Relevance
“…27 A second interaction is also taking place, though, in which the tip bias induces an image charge in the grounded sample, resulting in an electrostatic attraction that increases with the bias. We have found that in some materials, such as graphite 28 and freestanding graphene, 29 this attraction can result in physical movement of the sample, convoluting and often eclipsing any DOS measurement. Given that it is not a spectroscopy measurement, we call this measurement EM-STM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…27 A second interaction is also taking place, though, in which the tip bias induces an image charge in the grounded sample, resulting in an electrostatic attraction that increases with the bias. We have found that in some materials, such as graphite 28 and freestanding graphene, 29 this attraction can result in physical movement of the sample, convoluting and often eclipsing any DOS measurement. Given that it is not a spectroscopy measurement, we call this measurement EM-STM.…”
Section: Methodsmentioning
confidence: 99%
“…The large charge density of graphene pushes its surface (imaged by the STM tip) further out into the vacuum. 31 In a broader context, we are modeling the case where a normal force is continuously applied to the graphene as it approaches graphite. The two systems eventually begin to interact, and the graphene transitions to a layer of graphite.…”
Section: E Vertical Displacement Total Energy Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Xu et al demonstrated atomic control of strain in freestanding graphene using a local attractive force created at the STM tip. 10 Moreover, mechanical vibrations in suspended nanoribbons were generated by D. Garcia-Sanchez et al with sinusoidal variation of strains.…”
Section: Introductionmentioning
confidence: 99%
“…The starting point for us was the analysis of strain created by a scanning tunneling microscope (STM) on graphene [18]. There is a theory laid out on a structural continuum [22,11,12,13,14,15,16,17] that correlates structural deformations to URL: sbarraza@uark.edu (Salvador Barraza-Lopez) mechanically-induced gauges on Dirac fermions in 2+1 dimensions.…”
mentioning
confidence: 99%